2013
DOI: 10.1080/17429145.2013.833653
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of Arabidopsis thaliana roots between wild type and its salt-tolerant mutant

Abstract: Two-dimensional electrophoresis (2-DE) showed the variation expression of Arabidopsis thaliana root proteins between wild type and its salt-tolerant mutant obtained from cobalt-60 g ray radiation. Forty-six differential root protein spots were reproducibly presented on 2-DE maps, and 29 spots were identified by matrix assisted laser desorption ionization-time of flight/time of flight mass spectrometry (MS). Fifteen protein spots corresponding to 10 proteins, and 14 protein spots corresponding to 9 proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The analysis of PPI interaction networks was performed by the online STRING (search tool for recurring instances of neighboring genes) database (Version 11.0, released January 19, 2019) (http://string-db.org/). Growth conditions and harvest of Arabidopsis root According to previous publications (Guo et al 2014a;Kilian et al 2007), the ecotype Col-0 Arabidopsis seeds were germinated on the normal medium plate with 22/20°C day/night, 8/16 h light/dark cycle, 60 μmol•m −2 s −1 light intensity. After 7 days, the A. thaliana seedlings separately underwent the following stresses: the cold-stress condition (8°C), the osmotic stress condition (200 mmol•L −1 mannitol), the salt stress condition (150 mmol•L −1 NaCl), the wounding stress condition by punctuation of the leaves with needles, the drought stress condition by removing the lid of dish and exposing to a stream of air for 15 min, the UV stress condition by removing the lid of dish and irradiated with UV light for 15 min, the heat stress Figure 1.…”
Section: Gene Ontology Classification and Ppi Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of PPI interaction networks was performed by the online STRING (search tool for recurring instances of neighboring genes) database (Version 11.0, released January 19, 2019) (http://string-db.org/). Growth conditions and harvest of Arabidopsis root According to previous publications (Guo et al 2014a;Kilian et al 2007), the ecotype Col-0 Arabidopsis seeds were germinated on the normal medium plate with 22/20°C day/night, 8/16 h light/dark cycle, 60 μmol•m −2 s −1 light intensity. After 7 days, the A. thaliana seedlings separately underwent the following stresses: the cold-stress condition (8°C), the osmotic stress condition (200 mmol•L −1 mannitol), the salt stress condition (150 mmol•L −1 NaCl), the wounding stress condition by punctuation of the leaves with needles, the drought stress condition by removing the lid of dish and exposing to a stream of air for 15 min, the UV stress condition by removing the lid of dish and irradiated with UV light for 15 min, the heat stress Figure 1.…”
Section: Gene Ontology Classification and Ppi Networkmentioning
confidence: 99%
“…In our previous work, we focused on the salt-responsive molecules using A. thaliana as the model plant. The results indicated the differential molecules were involved in cell wall metabolisms and reactive oxygen species (ROS) scavenging (Guo et al 2014a). More importantly, the complicated cross-tolerances to differential stresses such as osmosis, water deprivation, heat, UV-light and wounding has been shown in A. thaliana (Guo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous publication (Guo et al 2014b), the ecotype Col-0 Arabidopsis thaliana seeds were germinated on the normal medium plate with 22/20°C day/night, 8/16 h light/dark cycle, 60 μmol•m-2s-1 light intensity. After 7 days,…”
Section: Growth Conditions and Harvest Of Arabidopsis Rootmentioning
confidence: 99%
“…In order to demonstrate the mechanisms of saltresponse, many researches have been performed with the model plant Arabidopsis (Guo et al 2019). Two-dimensional electrophoresis has been used to discover the differential Arabidopsis root proteins between wild type and salt-tolerance mutant, which identified 19 differential proteins related to signal transduction, redox homeostasis, and cell wall metabolism (Guo et al 2014b). Furthermore, phosphorylation variations of proteins from Arabidopsis root under salt stress also have been determined by Pro-Q Diamond stain.…”
Section: Introductionmentioning
confidence: 99%
“… Guo et al (2013) showed that 17 unique proteins differentially changed in abundance in response to NaCl in Arabidopsis roots. These identified proteins were believed to be involved in binding catalysts, signal transduction, transport, metabolism of cell wall and energy, and ROS scavenging and defense.…”
Section: Proteomics Approachmentioning
confidence: 99%